Assessment of Expressiveness in Poetry Reading Instruction Using the Historical Spice Route as Stimulus - Tika Himmatur Rosyidah; Wahyudi Siswanto; Imam Agus Basuki; Titik Harsiati; Karkono (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
Assessment plays a crucial role in evaluating students' mastery of learning materials and guiding instructional improvements. This paper presents a model of an assessment instrument tailored for poetry reading instruction at the junior high school level, using historical spice-themed poetry as an instructional stimulus. The assessment focuses on three key expressive elements: physical structure of the poem, reading performance, and emotional expression. Drawing on historical narratives about the Spice Route, the instrument provides contextual relevance that engages students both emotionally and intellectually. Findings highlight the importance of performance-based assessment in fostering students' expressive abilities and cultural understanding through poetry. The proposed rubric includes detailed descriptors for each assessment component and aligns with current curricular goals in language and cultural education.